Les conflits de temporalités dans la gestion du littoral à l'épreuve de la GIZC - Betty Queffelec; Fabienne Kervarec (Développement Durable et Territoires)
Integrative action process, the integrated coastal zone management (ICZM) has to deal with temporality conflicts in its implementation. It results from phase shift in rhythms and calendars. During an ICZM process, simultaneous long, middle and short term stakes get crossed. Then, it reveals temporality conflicts. But ICZM has a real potential to reduce this phenomenon. The ICZM long term framing feature added to its integrative feature, including its temporal dimension, have a potential to deal with those conflicts. However, many fences reduce yet a complete achievement of this potential.